In vitro antibacterial activities of crude extracts of nine plants on multidrug resistance bacterial isolates of wound infections - Muhammad Evy Prastiyanto; NI MADE BUNGA ANGGELIA DEWI; TUSY DIAH PRATININGTIAS; NI MADE RAI PRATIWI; ANGGIS WINDAYANI; EKA WAHYUNENGSIH; ASTUTI ASTUTI; ELVIRA AMIR; FANDHI ADI WARDOYO (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Prastiyanto ME, Dewi NMBA, Pratiningtias TD, Pratiwi NMR, Windayani A, Wahyunengsih E, Astuti, Amir E, Wardoyo FA. 2021. In vitro antibacterial activities of crude extracts of nine plants on multidrug resistance bacterial isolates of wound infections. Biodiversitas 22: 2641-2647. Wound infections caused by bacteria is a become serious health problems, multidrug resistance bacteria (MDR) have increased this problem more severely, and therefore, antibacterial agents from natural biological sources are necessary to overcome these problems. This study examined the antibacterial activities of nine plants, i.e. garlic (Allium sativum), Solo garlic (Allium sativum), Java plum leaf (Syzygium cumini), Java plum fruit (Syzygium cumini), lime (Citrus aurantifolia), Kaffir lime (Citrus hystrix), Siamese weed (Chromolaena odorata), mangosteen (Garcinia mangostana) and bitter melon (Momordica charantia), against MDR bacteria isolated from wounds. The antibacterial activities were evaluated using agar well diffusion assay to determine the inhibition zones, and microdilution method to determine the value of minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC). The best antibacterial activities were calculated as the most extensive inhibition zones with the smallest MIC and MBC values. Ethanol extracts from five plants (garlic, Solo garlic, Java plum (leaf), Kaffir lime and bitter melon) showed antibacterial activities against three MDR bacteria isolated from wounds. The bitter melon extract had the largest zones, 19.3 mm (methicillin-resistant Staphylococcus aureus [MRSA]), 10.6 mm (ESBL-producing Escherichia coli), and 13 mm (carbapenemase-resistant Pseudomonas aeruginosa [CRPA]) with the smallest MIC and MBC values against MRSA (3.12 and 25 mg/mL), ESBL- producing E. coli (12.25 and 50 mg/mL), and CRPA (6.25 and 25 mg/mL). This concludes that bitter melon has the potential to be developed as an antibacterial agent, particularly against MRSA strains, ESBL-producing E. coli, and CRPA that cause wound infections. Further in vivo research and the discovery of modes of action are needed to explain the antibacterial effects.